Effect of nanoscale precipitation on strengthening of ferritic ODS Fe–Cr–Al alloy. (October 2013) - Capdevila, C.; Chao, J.; Jimenez, J. A.; Miller, M. K.
Abstract : The kinetics of Fe rich α and Cr rich α ′ phase separation during aging of Fe–Cr–Al oxide dispersion strengthened alloys have been analysed with a combination of atom probe tomography and thermoelectric power measurements. The slight lattice parameter decrease measured by X-ray diffraction after thermal aging was associated with a lattice misfit between the emerging α and α ′ domains. The elastic strain associated with this misfit and the different elastic moduli for the α and α ′ phases would produce an increase in internal stresses that would retard the motion of dislocations and thus would be the main cause for the strengthening.